Pastoral herd management,drought coping strategies, and cattle mobility in southern Kenya - Butt, B.; Shortridge, A.; Winkler Prins, A.M.G.A. (Informa UK Limited, 2009)
Livestock mobility facilitates opportunistic grazing management strategies that pastoralists employ to counter environmental variability in rangelands. One such strategy is moving livestock to temporary camps that are closer to areas of underutilized forage during times of drought. In areas where pastoralists graze near large protected areas, movement into protected areas, where both forage quantity and quality are higher, is also a common strategy. The aim of this study is to test hypotheses of herd relocation and effects of seasonality and herd size on spatially explicit parameters of cattle mobility for Maasai pastoralists along the northern border of a protected area in Kenya. Modified Global Positioning System (GPS) collars were placed on cattle from ten Maasai households that recorded three parameters of mobility for hundreds of grazing orbits from August 2005 to August 2006. Data were grouped by two constraints—seasonality and herd size—and tested against the two types of enclosure locations (temporary camps and permanent settlements). Hypotheses were formed on the basis of the current knowledge within the literature and analyzed using a series of analyses of variance. Results suggest that household relocation reduces the stress faced by pastoralists and their cattle during the drought by (1) lowering the average total daily distance and time traveled by cattle, (2) directing cattle toward the protected area, and (3) concentrating cattle grazing in distinct areas within the protected area. Herd size was found to have no effect on duration of travel for pastoralists that choose not to relocate during the drought. The research demonstrates how the use of modified low-cost GPS collars can be an effective tool for capturing parameters of mobility and for inferring pastoralist-livestock-rangeland relationships.